برنامج تدريبي في مهارات الوعي الصوتي قائم على التدريس التأملي وأثره في تنمية الثروة اللغوية وطلاقة الأداء التدريسي لدى معلمات محو الأمية - عيد، أيمن عيد بكري محمد (جامعة بني سويف - كلية التربية, 2021)
الهدف الرئيس للبحث الحالي يتمثل في إكساب معلمات محو الأمية مهارات الوعي الصوتي باستخدام التدريس التأملي وقياس أثره في تنمية الثروة اللغوية، وطلاقة الأداء التدريسي. وقام الباحث بإعداد الأدوات الآتية: اختبار الوعي الصوتي واختبار الثروة اللغوية لمعلمات محو الأمية، وبطاقة ملاحظة طلاقة الأداء التدريسي لمعلمات محو الأمية، وبطاقة ملاحظة مهارات التدريس التأملي لمعلمات محو الأمية، وبرنامج تدريبي في مهارات الوعي الصوتي باستخدام التدريس التأملي. تم تطبيق البرنامج التدريبي على عينة من معلمات محو الأمية بمركز أهناسيا بمحافظة بني سويف في الفترة من (20/3/2018 إلى 3/4/2018)، ومن أهم النتائج التي توصل إليها البحث: فعالية البرنامج التدريبي القائم على مهارات التدريس التأملي في تنمية الثروة اللغوية وطلاقة الأداء التدريسي لدى معلمات محو الأمية
Assistant Professor at the National Center for Educational Research and Development, Curriculum and teaching methods of the Arabic language The main objective of the current search is to give the women teachers for eradicating illiteracy phonological awareness using Reflective Teaching and measure its impact on vocabulary development skills, and fluency teaching performance. The researcher prepared the following tools: A list of appropriate Reflective Teaching skills for women teachers of illiteracy, and the list of phonological awareness skills necessary for teachers literacy, and observation card for the fluency of teaching performance parameters literacy card, and the teaching meditative skills for teachers of illiteracy observation card, vocabulary test for illiteracy and training program in phonological awareness using Reflective Teaching skills. The training program has been applied to a sample of women teachers at the eradicating illiteracy center Ahnasia , Bany Swaif governerate, in the period from: 20/3/2018-3/4/2018, and among the most important findings of the research :the effectiveness of the training program in vocabulary development and fluency of teaching performance, and skills of Reflective Teaching.
Keywords: اللسانيات الصوتية -- المهارات اللغوية -- البرامج التدريبية -- التدريس التأملي -- محو الأمية